Penerapan strategi pemasaran dan kualitas pelayanan dalam meningkatkan penjualan mobil bekas pada Showroom Berkah Mobilindo - Sabrina, Tifani; Wibowo, Wijanarko Agus (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2026)
This study examines the implementation of marketing strategies and service quality in increasing used car sales at Berkah Mobilindo Showroom. The research employed a qualitative descriptive method through interviews with the owner, employees, and customers. The findings indicate that marketing strategies, such as market selection, competitive pricing, and direct communication with customers, effectively attract buyers. Meanwhile, service quality aspects, including reliability, responsiveness, assurance, and empathy, positively influence customer satisfaction. Overall, the combination of marketing strategies and good service quality contributes to increased sales and business growth.